2018
DOI: 10.1002/cbic.201700599
|View full text |Cite
|
Sign up to set email alerts
|

Alanine and Lysine Scans of the LL‐37‐Derived Peptide Fragment KR‐12 Reveal Key Residues for Antimicrobial Activity

Abstract: The human host defence peptide LL-37 is a broad-spectrum antibiotic with immunomodulatory functions. Residues 18-29 in LL-37 have previously been identified as a minimal peptide (KR-12) that retains antibacterial activity with decreased cytotoxicity. In this study, analogues of KR-12 were generated by Ala and Lys scans to identify key elements for activity. These were tested against a panel of human pathogens and for membrane permeabilisation on liposomes. Replacements of hydrophobic and cationic residues with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 38 publications
4
44
1
Order By: Relevance
“…In this case the dimers are just 2-3 times as potent as the monomers. The 23-fold difference in EC50 for KR-12 in either liposome system is not mirrored in the antimicrobial assay ( Table 2), and supports the previous proposition that membrane permeabilization is not the sole mechanism of action for the KR-12 monomer on bacteria (Gunasekera et al, 2018).…”
Section: Dimers Disrupt Lipid Membranes With Enhanced Efficacysupporting
confidence: 84%
See 4 more Smart Citations
“…In this case the dimers are just 2-3 times as potent as the monomers. The 23-fold difference in EC50 for KR-12 in either liposome system is not mirrored in the antimicrobial assay ( Table 2), and supports the previous proposition that membrane permeabilization is not the sole mechanism of action for the KR-12 monomer on bacteria (Gunasekera et al, 2018).…”
Section: Dimers Disrupt Lipid Membranes With Enhanced Efficacysupporting
confidence: 84%
“…Substitutions with Lys increased activity as long as the resulting increase in cationic density did not disrupt the amphiphilic disposition of the helical structure. Key positions were identified as Gln5 and Asp9, which when replaced with Ala or Lys increased broad-spectrum activity up to 8-fold against S. aureus, P. aeruginosa, and C. albicans (Gunasekera et al, 2018). In line with previous work (Wang, 2008;Wang et al, 2008), KR-12 showed weak cytotoxic activity with only a 13% loss of human cell line viability at the maximum concentration of 80 µM.…”
Section: Introductionsupporting
confidence: 82%
See 3 more Smart Citations